Pembuatan Akarisida Organik di Kelompok Tani Sumber Urip-1 Desa Wonorejo Kecamatan Poncokusumo Kabupaten Malang - Krisno Budiyanto, Moch. Agus; Waluyo, Lud; Rahadjanto, Abdulkadir (Universitas Pendidikan Ganesha, 2020)
Farmers who apply organic farming still have problems related to the knowledge about the making and use of organic acaricide, so it is necessary to conduct Community Partnership Program (Pengabdian kepada Masyarakat/PkM). PkM aims to provide assistance to partners so that there are improvements in terms of, (1) mastery of organic acaricide production methods of members of organic farmer groups who become partners and (2) master the method of using organic acaricide members of organic farmers who become partners. PkM's partners are Sumber Urip-I Farmers Group Wonorejo Village, Poncokusumo Sub-district, Malang Regency. PkM implementation method consists of 2 main activities, as follows: 1) Training of organic acaricide manufacture from local raw materials and 2) Training and mentoring the use of organic acaricides. Through a series of training and mentoring activities: 1) all members (100%) of PkM partners have mastered organic acaricide making methods and 2) all members (100%) of PkM partners have mastered the use and are able to increase organic acaricide production.